Taboo Words in Birds of Prey Movie (2020): Sociolinguistics Study - Indah Dwi Anjani; Hero Gunawan (Budapest International Research and Critics University, 2022)
This study aims to analyze the types of taboo words and the function of taboo words that used in Birds of Prey Movie (2020). This research use types of taboo words theory from Battistella (2005) and the functions of taboo words from Wardaugh (2000). The method used in this research is descriptive qualitative. The data used were taken from Birds of Prey movie (2020). The findings demonstrated that there are four types of taboo words found from 67 data, namely epithet 12 (18%), obscenity 42 (62,6%), vulgarity 6 (9%), and profanity (10,4%). Moreover, there are four functions that found in this research, namely to draw attention to oneself 39 (58,2%), to show contempt 11 (16,4%), to mock authority 8 (12%), and to be provocative 9 (13,4%)..